Analisis Kinerja Keuangan Bumdes Rejo Mulyo Desa Sidomulyo Kecamatan Ngadirojo Kabu-paten Pacitan - Madhani, Ryonti; Ludigdo, Unti (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
This study evaluates the financial performance of Rejo Mulyo Village Owned Enterprise (BUMDes) of Sidomulyo Village, Ngadirojo District, Pacitan Regency between 2019 and 2021. Although BUMDes Rejo Mulyo depends on its financial health on its financial performance, it never measures its financial performance, if not all of, its existing financial reports have never been the factor in decision-making. A percentage can be used to evaluate financial performance outcomes in accordance with predefined standards. The data of this study are collected from documentation, interviews, and observations, and analyzed by data reduction techniques, data presentation, and conclusion. The findings exhibit that BUMDes Rejo Mulyo still has trouble meeting its short-term debt commitments, judged by its liquidity as determined by the current ratio. The debt-to-equity ratio, measuring solvency, reveals highly positive outcomes. Return on equity, a measure of profitability, demonstrates that BUMDes Rejo Mulyo has done a decent job at turning a profit, and good results are evidenced in the return on assets.